Excellent And Sustainable Tourism Management Through The Baldrige Criteria: Case Study: Mangunan Orchard Tourism Attraction - Tri Eko Yudiandri; Agung Sulistyo (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2022)
Optimizing organizational performance has a positive impact on the services provided. Various steps need to be taken in an effort to create a sustainable business. Organizational excellence is inseparable from several main factors, such as: performance, customer satisfaction, leadership, process management, employee involvement, learning, innovation, and social responsibility. Organizations must be able to assess their performance to explore various opportunities and be able to put themselves in a competitive situation. The Baldrige Criteria are a guide for organizations to evaluate performance and create superior and world-class management. This criterion consists of seven pillars, namely: leadership; strategic planning; focus on consumers and markets; analysis and knowledge management; focus on human resources; business process management; and results. This research was conducted to analyze the application of the Baldrige Criteria to the Mangunan Fruit Garden tourist attraction as an effort to create superior and world-class tourism management. A qualitative, descriptive research design was used in this study and was combined with the Baldrige Criteria instrument. Collected data for this study through in-depth interviews with several informants from management and employees. The results of the study explained that the management of the Mangunan Orchard was not in accordance with the Baldrige Criteria. Tourist attraction managers need to design the right strategy to create superior and world-class organizational performance.